AN OVERVIEW OF ANNAKAADI (RICE VINEGAR) IN SIDDHA SYSTEM OF MEDICINE (International Journal of Ayurveda and Pharma Research, 2020)
Siddha system of medicine established by ancient Siddhars is based on Dravidan (Tamilian) culture. In this system of medicine some peculiarities are there like Annakaadi (rice vinegar), Amuri (Siddha elixir), Jayaneer (salty extraction), Theeneer (distillates) which are used as medicines for treating various illness and used as precursor for higher order medicine. Nowadays these special things are away from our day today practice because lack of knowledge, non availability of ingredients, unknowing the preparation techniques, long duration for preparation, etc. Annakaadi is one of the Siddha resources, obtained from fermented rice water. In Siddha system of medicine, the Annakaadi plays a vital role in the purification process of various raw materials like Naabi (Aconitum ferox), Serankottai (Semecarpus anacardium), iron, zinc, arsenic, copper sulphate, Palagarai etc., in medicine preparation especially higher order medicine (Parpam, Chenduram) preparation, in medicine administration as adjuvant, and in external therapies. Clinically it is used for the management of Urinary Tract Infection, Diarrhoea and Gastritis. Nowadays the practitioners used commercially available vinegar instead of Annakaadi for their practice but commercially available vinegar is totally different from the Siddha preparation of Annakaadi. This study is aimed to review the preparation method and importance of Annakaadi in Siddha system of medicine from various ancient literatures. This study concluded that the Annakaadi in Siddha, it is an essential one for detoxification, preservation, preparation of higher order medicine and treat the emerging conditions. Further analytical and clinical studies are to be carried out to confirm its importance and efficacy.